Nanomedicine: promises and pitfalls 1 - Webster, Thomas J. (Henry Stewart Talks, 2015)
Nanotechnology in regenerative medicine, Nano-structured medical materials, Surface properties & energy control at the nano level, Injectable bone healing materials, Anodized titanium